Effect of different land configurations and crop geometry with levels of fertilizer on sunflower productivity under rainfed condition: Effect of different land configurations and crop geometry with levels of fertilizer on sunflower productivity under rainfed condition - T SELVAKUMAR; L RAJENDRAN; R SASIKALA (Journal of Oilseeds Research, 2023)
A field experiment with the objective to determine the response of sunflower to varying planting geometry and fertilizer levels under different land configurations was conducted under rainfed condition. The experiment was laid out in split plot design consisting of twelve treatments (Four main and three sub treatments) and replicated thrice. The entire period of cropping period received the adequate rainfall for the growth and development. The economics revealed that the land configuration ridges and furrow sowing with 100 % RDF recorded higher net return (Rs. 8,517/ha) and BCR (1.25). Hence, it concluded that under red loamy soil, sowing of sunflower with a spacing of 60 cm x 30 cm in ridges and furrow land configuration with application of 100 % RDF is highly suitable under rain fed condition to attain maximum yield with more profit.